A prospective study of systemic sclerosis-related digital ulcers: prevalence, location, and functional impact. (November 2013) - Ennis, H; Vail, A; Wragg, E; Taylor, A; Moore, T; Murray, A; Muir, L; Griffiths, CEM; Herrick, AL
<x xml:space="preserve">Abstract</x> Objectives: Although digital ulcers (DUs) are common in patients with systemic sclerosis (SSc), prevalence estimates vary, and functional impact and pathophysiology have been relatively little studied. We investigated the point prevalence of all DUs (both digital-tip and extensor) in a cohort of patients with SSc, testing the hypothesis that both digital-tip and extensor ulcers are associated with functional impairment. Method: Over a 12-month period, patients attending an SSc clinic for annual review were assessed by specialist nurses: active DUs were documented and the Hand Mobility in Scleroderma (HAMIS) test performed. Patients also completed the Scleroderma Health Assessment Questionnaire (SHAQ), the Scleroderma Functional Index (SFI), and the Cochin Hand Function Scale (CHFS). Results: A total of 25 active DUs (nine digital-tip and 16 extensor surface) were found in 15 of the 148 patients recruited, giving a prevalence for each ulcer type of 6% and an overall point prevalence of 10%. HAMIS scores were higher (indicating greater impairment) in those with active DUs than in those without: left hand difference 8.8 points [95% confidence interval (CI) 3.2–14.5], p = 0.002; difference significant for extensor as well as digital-tip ulcers. Active DUs were associated with higher visual analogue scale (VAS) scores for pain (p = 0.04), DUs (p < 0.001), and 'overall' assessment (p = 0.03). Conclusions: Extensor surface ulcers have the same prevalence as digital-tip ulcers in patients with SSc, and are equally disabling. Clinical trials should therefore include both categories of DUs.